Business Development Strategy for Smart Watering Product of PT. Hidroponik Padjadjaran Indonesia - Vidianti Rahmi, Hasna; Perwitasari, Sophia Dwiratna Nur; Pratopo, Lukito Hasta (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The urban hydroponic cultivation trend presents a promising opportunity for the advancement of hydroponic agro-industry within Indonesia. This phenomenon has been catalyzed by the innovation of the Smart Watering hydroponic kit introduced by PT. Hidroponik Padjadjaran Indonesia. The Smart Watering system, founded on the principles of self-watering irrigation and electricity-free operation, has unlocked new possibilities in hydroponic agriculture. This study aims to assess the formulation of strategic initiatives for the sustainable growth and continuity of Smart Watering business operations. Employing qualitative and quantitative research techniques, including IFE-EFE, BMC-SWOT, and AHP analyses, the investigation reveals that the IFE matrix scores 2.11, while the EFE matrix scores 2.70, positioning the company in quadrant V. Subsequently, a BMC-SWOT analysis identifies twelve potential strategies, which are further evaluated through AHP analysis to determine priority strategies. The findings underscore market penetration (0.689) as a key strategic criterion, with the top-priority strategy, W02 (0.156), emphasizing active engagement with local and regional hydroponic communities to foster network expansion and enhance human resource competencies. These findings provide a foundation for the implementation of growth and sustainability strategies in hydroponic agro-industry enterprises. Keywords: Business Development Strategy, Hydroponic, IFE-EFE, BMC-SWOT, AHP